Vaccine injury compensation: the Israeli case - Shelly Kamin-Friedman; Nadav Davidovitch (BMC, 2021)
Abstract Background Following other countries, Israel passed the Vaccine Injury Compensation Law in 1989, which provides for compensation to vaccine recipients who had suffered injuries without proving negligence. In 2021, after deliberations between the ministries of health and of finance Covid-19 vaccines (administered from the beginning of the campaign on December 20, 2020 and up to December 21, 2022) were included within the compensation law. The current study aims to examine the objectives of Israel's Vaccine Injury Compensation Law, at the time of its enactment, and to explore barriers to their fulfillment. These issues are especially relevant in light of the discussions held on the option for liability exemption which excludes the possibility of redress from the Covid-19 vaccine manufacturers in case of injury attributed to the vaccine, and considering the heavy burden of proof required in standard tort law. Methods The study employed a qualitative methodology which made use of both content analysis of relevant documents and in-depth interviews. Results In passing the Vaccine Injury Compensation Law, legislators sought to assist vaccine recipients who had suffered injuries by both lowering their burden of proof as well as establishing a short and efficient procedure for deliberating their claims. Furthermore, legislators believed that the assurance of compensation to vaccine recipients who had suffered injuries would help to encourage a high rate of vaccination compliance. An examination of the law's implementation over time revealed that the aforementioned goals were not attained. Conclusions Implementation of the law since its enactment missed the opportunity to fulfill its original purposes to promote public health fundamental principles of fairness and solidarity. In addition, the adversarial proceedings as well as some of the law's provisions have the potential to undermine public trust in the State's willingness to grant compensation for injuries that are attributed to vaccines and thereby subvert the law's pivotal objective of promoting trust and vaccine compliance. We suggest that allowing circumstantial evidence as to an association between vaccine and an injury, transitioning to administrative deliberation, making available to the public details of cases where compensation was awarded, as well as other possible emendations would help it better reflect the values of fairness and solidarity that underlying the law's purpose. These would also promote the level of trust in healthcare authorities which is essential to preserving high vaccine coverage.